Stock Market Reactions to Automotive Product Launches : An Event Study of India’s Leading Manufacturers - Chowdhury, Arnav; Jain, Megha (Indian Journal of Research in Capital Markets, 2025)
This study examined whether major passenger-vehicle product launch announcements by Tata Motors, Mahindra and Mahindra, Maruti Suzuki, and Hyundai Motor India generated abnormal stock-market returns in India during 2015–2025, and whether investor reactions differed by segment (EVs vs. premium SUVs). It applied an event-study design in which abnormal returns were estimated using a market model and then aggregated into cumulative abnormal returns (CARs) over a symmetric –30 to +30 trading-day window around each launch. A standard market model event-study framework was implemented to estimate expected (normal) returns and derive abnormal returns attributable to the announcement. These were then aggregated to compute cumulative abnormal returns (CARs) over the event window. Temporal regression-based diagnostics were used to assess structural change, and ANOVA was used to test whether mean CARs differed across product segments. Overall market receptivity was weak, with a mean CAR of −0.36% (p = 0.10) and 63.3% of launches showing negative CARs. A premium SUV launch (XUV 3XO) exhibited stronger positive performance relative to mass-market and EV launches, and a structural break was observed around 2020, indicating relatively improved post-pandemic market reactions. The findings suggested that while product launches remained central to long-term strategy, announcement effects did not reliably translate into immediate positive trading signals for investors. Managers were advised to emphasize execution and delivery of premium innovations rather than relying on short-run announcement-driven valuation effects. The study contributed emerging-market evidence by isolating announcement-related valuation effects in India’s automotive sector and comparing market responses to ICE-model introductions versus EV launches across a decade of product-cycle transitions.